Our nation (Macmillan/McGraw - Hill, 2003)
In this text book you will meet special people and learn many important things. The stories you read willl help you understand some important words thet define what means to be a good citizen. These words are listed below. They help us understand how to be better citizens in our home, neighborhood, school, community, country, and world